iTRAQ-based protein profiling provides insights into the central metabolism changes driving grape berry development and ripening - Martínez-Esteso, María José (BioMed Central, 2013)
BACKGROUND: Grapevine (Vitis vinifera L.) is an economically important fruit crop. Quality-determining grape components such as sugars, acids, flavors, anthocyanins, tannins, etc., accumulate in the different grape berry development stages. Thus, correlating the proteomic profiles with the biochemical and physiological changes occurring in grape is of paramount importance to advance in our understanding of berry development and ripening processes. RESULTS: We report the developmental analysis of Vitis vinifera cv. Muscat Hamburg berries at the protein level from fruit set to full ripening. An iTRAQ-based bottom-up proteomic approach followed by tandem mass spectrometry led to the identification and quantitation of 411 and 630 proteins in the green and ripening phases, respectively. Two key points in development relating to changes in protein level were detected: end of the first growth period (7 mm-to-15 mm) and onset of ripening (15 mm-to-V100, V100-to-110). A functional analysis was performed using the Blast2GO software based on the enrichment of GO terms during berry growth. CONCLUSIONS: The study of the proteome contributes to decipher the biological processes and metabolic pathways involved in the development and quality traits of fruit and its derived products. These findings lie mainly in metabolism and storage of sugars and malate, energy-related pathways such as respiration, photosynthesis and fermentation, and the synthesis of polyphenolics as major secondary metabolites in grape berry. In addition, some key steps in carbohydrate and malate metabolism have been identified in this study, i.e., PFP-PFK or SuSy-INV switches among others, which may influence the final sugar and acid balance in ripe fruit. In conclusion, some proteins not reported to date have been detected to be deregulated in specific tissues and developmental stages, leading to formulate new hypotheses on the metabolic processes underlying grape berry development. These results open up new lines to decipher the processes controlling grape berry development and ripening.